Exploring the secrets of virus entry: the first respiratory syncytial virus carrying beta lactamase - De Ávila-Arias, Marcio; Villarreal-Camacho, Jose Luis; Cadena-Cruz, Christian; Hurtado-Gómez, Leidy; Costello, Heather M.; Rodriguez, Alexander; Burgos-Florez, Francisco; Bettin, Alfonso; Kararoudi, Meisam Naeimi; Muñoz, Amner; Peeples, Mark E.; San-Juan-Vergara, Homero (Frontiers in Microbiology, 2024)
The respiratory syncytial virus (RSV) is the representative member of the orthopneumovirus genus and is the common cause of respiratory diseases in children under 5 years old. Each year, 160,000 children die because of the infection.Currently, there is only partial knowledge and understanding of the mechanisms that facilitate virion entry. One of the reasons is that we did not have engineered virions to functionally study the stages involved in their entry. In this report, we present the first recombinant RSV carrying the beta-lactamase enzyme (BlaM) as a structural protein, which is fused at the C-terminal level with the RSV-P phosphoprotein (P-BlaM). Viral entry is recognized by the shift in fluorescence to the hydroxycoumarin channel due to the breakage of the beta-lactam ring and consequent disruption of the Förster resonance energy transfer (FRET) in the CCF2 fluorescence substrate (hydroxycoumarin-beta-lactam ring-fluorescein). Using the rgRSV-P-BlaM virion, we demonstrated that the flavonoid quercetin inhibits viral entry by affecting virion fusion with the plasma membrane. Additionally, ulixertinib, a competitive inhibitor of ERK-1/2-dependent kinase activity, reduces virion entry, strongly suggesting that some of the phosphorylated ERK-1/2 substrates facilitate viral entry due to their role in cell membrane dynamics. The development of rgRSV-P-BlaM not only provides a tool to expand our knowledge of RSV entry but also serves as a roadmap for designing similar approaches for metapneumoviruses or other paramyxoviruses.In this study, we present the development of engineered RSV to the onset of entry as soon as it is happening. This will allow us to identify the contribution of cellular mechanisms, pathways, and proteins in RSV entry. Additionally, it will help identify new antivirals and could contribute to vaccine development. Finally, it will serve as a roadmap for the equivalent design to study the entry mechanism of other orthopneumoviruses, such as metapneumovirus